FACTORS INFLUENCING WOMEN'S ENGAGEMENT IN GOVERNANCE IN EDO STATE OF NIGERIA - Ainabor, Augustine Eguavuon; Ibe-Enwo, Grace Iyi; Zakiya, Annisa Luthfi (Universitas Jember, 2024)
ABSTRACTThe research examined the factors that influence women's engagement in governance, using Edo State, Nigeria, as a case study. It investigated the amount of influence of women's participation in government in Edo State, Nigeria. It also analyzed the extent to which education influences women's engagement in Edo State governance in Nigeria. To meet the stated goals, two hypotheses were developed to guide the investigation. Data was collected mostly through a questionnaire. The study's population consisted of 4,625 prominent lawmakers from Edo State's three senatorial districts, with a Taro Yamani formula-determined sample size of 368. The Chi-Square(X2) test of proportion was adopted in the analysis of data. After statistically analyzing the data obtained from the primary source, it was found that there is low women participation in the governance of Edo State, Nigeria. It was also discovered that there is a link between women's educational attainment and their poor engagement in government in Edo State, Nigeria. The findings of this study suggest that state governments should take policy action to encourage more women to engage in governance. The document advocated, among other things, that the Edo State government foster girl-child and women's education as a deliberate strategy to ensure that more women have access to quality education that will prepare them to compete with males in the state's politics and governance.Keywords: Education, Governance, Politics, Women Participation